Important requirements for the selection of internal standards during the development of desorption/ionization assays for drug quantification in biological matrices: a practical example - Fresnais, Margaux; Karabulut, Seda; Abou Zeed, Yasmin; Ungermann, Johannes; Benzel, Julia; Pajtler, Kristian Wilfried; Pfister, Stefan; Haefeli, Walter E.; Burhenne, Jürgen; Longuespée, Rémi (Molecules, 2022)
Desorption/ionization mass spectrometry (DI-MS) approaches allow for the rapid quantification of drugs in biological matrices using assays that can be validated according to regulatory guidelines. However, specific adaptations must be applied to create reliable quantification methods, depending on the approach and instrumentation used. In the present article, we demonstrate the importance of the molecular weight, the fragmentation pattern, and the purity of the internal standard for the development of matrix-assisted laser desorption/ionization (MALDI)-ion mobility (IM)-tandem MS and MS/MS methods. We present preliminary results of method development for the quantification of selinexor in microdialysis fluids with a stable isotopically labeled internal standard. In addition, we discuss the selection of internal standards for MALDI-MS assays using different instrumentations.
Gesehen am 31.03.2022